Responsibility and pandemic: Creating a moral world - Caviglia Marconi, Alessandro (2021)
This article addresses the question of responsibility in contexts such as pandemics and other diseases or damages not caused by the agents involved, distancing itself from  phenomenological classical approaches. In order to do this, firstly, it undertakes the task of defining the concept of “responsibility” as a moral duty that arises from the relationship between broad duties and strict duties. Secondly, it takes distance from the republican approach which, inspired by the idea of freedom and justice as non-domination, defines responsibility as the duty that an individual has for the harm caused to another person. By going beyond this approach, the concept of responsibility is broadened so it reaches an individual for damages that were not caused by that person but can be avoided or compensated for. This concept also makes it possible for someone to assume responsibility by proclaiming itself as a moral person actively. Then, it explores the sense in which this approach places the agents before the opening of a “moral world” and how this world is inserted in the field of civil society through the generation of “trust networks”. Finally, the article concludes with an overview of how this idea of responsibility is applied in the context of pandemics such as Covid-19.